SUSTAINING COMPETITIVE ADVANTAGE DURING COVID-19 PANDEMIC: A PRELIMINARY CASE STUDY OF AEROSPACE MANUFACTURING INDUSTRY IN MALAYSIA - Putri Rozita Tahir; Masnita Abdul Ghani; Nurhanan Syafiah Abdul Razak, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The coronavirus (Covid-19) hits the world at a stage where companies plans are affected due to unplanned business disruptions and operations and the aerospace manufacturing industry is one of the industries that was hit severely. This paper is a preliminary attempt to investigate the impact of COVID-19 on the competitive advantage of one of the aerospace manufacturing companies as a case study. Through a comprehensive literature study and survey, this paper presents an interpretation of competitive advantage theory where the research framework presents the impact of internal and external influences on a company’s competitive advantage and whether strategic management mediates the impact. It illustrates the general concepts and development of hypotheses using the internal and external influences and strategic management. Quantitative analysis using survey will be used to collect and analysis of data from 30 leaders and executives that have been chosen for this study using PLS SEM. It is expected that this study will present a guide that illustrates how theories, general concepts and processes can be managed, allowing strategic management personnel to understand their market position and, from there, identify where the future direction.